Podcast: Media Pembelajaran IPS yang Menyenangkan bagi Peserta Didik Kelas V SDN Klepu Patuk di Masa Pandemi - Tuti Allawiyah; Elsa Putri Ermisah Syafril (Proceedings Series on Social Sciences & Humanities, 2022)
The Covid-19 pandemic that has hit the world has paralyzed the activities of almost all life sectors, including the education. Face-to-face teaching and learning activities have been abolished for quite a long time so that it becomes a tough challenge for teachers. One of the media that can be used as an alternative to online learning is podcasts. The aims of this study are: (1) to explain the social studies learning conditions during the pandemic for fifth grade students at SDN Klepu Gunungkidul; (2) to explain the social studies learning during the pandemic using podcasts for fifth grade students at SDN Klepu Gunungkidul; (3) to know the reasons why podcasts is become fun media of social studies learning for fifth grade students at SDN Klepu Patuk during the pandemic. This research uses a qualitative design with a case study approach. The data sources are 8 students of fifth grade at SDN Klepu Gunungkidul. The data collection techniques are observing communication via WhatsApp, interviews and documentation. The results of observations and interviews are then reduced to several important notes that provide a more specific picture. Furthermore, the results of the reduction are organized and arranged in the form of data presentations so that the relationship patterns are easier to understand and then drawn into conclusions. The results of this study are: (1) learning during the pandemic has made it difficult for teachers to convey material in a fun way, especially when learning is done online. (2) The teacher designs a fun online learning process during the covid-19 pandemic through podcasts so that students are very enthusiastic about participating in lessons (3) The use of podcast media as a learning media makes social studies learning more fun because students can view and listen to the information simultaneously through podcasts. It makes students' interest in learning online become increasing.